Preface - Joana Caetano (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
It is with great pleasure that the Editors introduce VIA PANORAMICA Vol. 13 N.º 1: The Dispossessed: 50 years since 50 years hence | A Journey Towards Utopian Science Fiction.